Persistent foot-and-mouth disease virus infection of the bovine nasopharynx is associated with suppression of innate and cellular immunity - Benedikt Litz; Florian Pfaff; Leonie F. Forth; Sara Hägglund; Jean-François Valarcher; Martin Beer; Michael Eschbaumer (PLoS ONE, 2026)
Foot-and-mouth disease is a devastating disease of cattle that is caused by foot-and-mouth disease virus (FMDV). After acute infection, FMDV persists in the upper respiratory tract of about 50% of infected cattle. The persistent infection is characterized by very localized viral replication in the absence of clinical signs, but the underlying mechanisms are still not clear. In our study, we investigated tissue samples collected from 20 cattle which had been experimentally infected with FMDV O/FRA/1/2001. In 17 animals, the infection persisted for longer than 28 days. Epithelial tissue from the dorsal nasopharynx and the dorsal soft palate (DSP), the two main locations for persistent infection, was collected at necropsy. Five biological replicates from each animal and location were screened by FMDV specific RT-qPCR, and subsets of the samples were selected for transcriptome sequencing (n = 52) and protein mass spectrometry (n = 18). There was a good correlation between the expression patterns identified by the transcriptomic and proteomic analysis. Higher loads of viral genome were detected in DSP samples. Overexpression of cellular markers for follicle-associated epithelium (FAE) and downregulated genes of epithelial integrity and keratinization correlated with viral genome loads, confirming the microanatomic localization of persistent FMDV infection in follicle-associated epithelium (FAE) in lymphoid tissue of the nasopharynx. An upregulation of genes which negatively influence T-cell responses indicates a T-cell exhaustion, most likely caused by prolonged immune stimulation. Moreover, decreased expression levels of RIG-I and TRAF6 probably resulted in inhibited detection of viral RNA by the innate immune system and ultimately an impeded type I interferon response. These observations are in line with the hypothesis that FMDV actively suppresses the local immunity in FAE to maintain a persistent infection in the bovine nasopharynx.